Cor Triatriatum Dexter with Noncompaction of Right Ventricle and Complete Heart Block: An Unholy Trinity - Bhandari, Monika; Pradhan, Akshyaya; Vishwakarma, Pravesh; Sethi, Rishi (International Journal of Angiology, 2021)
Cor triatriatum (CT) or a triatrial heart is a rare congenital anomaly in which one of the atrial chambers is divided by a fibromuscular membrane. Of the two variants, CT dexter (right-sided CT) is still further rare than CT sinister (left-sided CT). Although CT sinister presents with features of left heart obstructive disease mimicking mitral stenosis, CT dexter is usually asymptomatic and is found incidentally on imaging. Here, we present a patient with an unusual case of complete heart block who was found to have CT dexter along with right ventricular noncompaction on imaging.
Keywords: cor triatriatum; echocardiography; syncope; permanent pacemaker